Third-Degree Atrioventricular Block in Clinically “Silent” Acute Myocardial Infarction - Damay, Vito (Fakultas Kedokteran Universitas Pelita Harapan, 2016)
Third-degree atrioventricular (AV) block also termed complete heart block is present when there is complete absence of conduction between atria and ventricles. In adults the most common causes are acute myocardial infarction and age-related degeneration of conduction system. Incidence of conduction block is reported to be 25-30 % in the setting of acute myocardial infarction (AMI) and is 2 to 3 times as commonly associated with inferior than anterior infarction. Proper diagnosis involves noninvasive diagnostic tests (12 lead electrocardiogram (ECG), Holter ECG, or stress/exercise ECG).Keywords: third-degree AV block, complete av block, acute myocardial infarction